2022
DOI: 10.3390/jof8111203
|View full text |Cite
|
Sign up to set email alerts
|

Diversity among Lasiodiplodia Species Causing Dieback, Root Rot and Leaf Spot on Fruit Trees in Egypt, and a Description of Lasiodiplodia newvalleyensis sp. nov.

Abstract: Lasiodiplodia (family Botryosphaeriaceae) is a widely distributed fungal genus that causes a variety of diseases in tropical and subtropical regions. During 2020–2021, a routine survey of fruit tree plants was conducted in five Egyptian Governorates, and fresh samples exhibiting dieback, decline, leaf spot and root rot symptoms were collected. Collection from eight different symptomatic leaves, twigs, branches and roots of fruit trees yielded 18 Lasiodiplodia-like isolates. The sequencing data from the interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…An Egyptian study identified Lasidiplodia spp. as a causative agent of citrus mortality (El-Ganainy et al, 2022). These studies show that citrus dieback is a multifactorial disease that requires further investigation and management.…”
Section: Introductionmentioning
confidence: 79%
“…An Egyptian study identified Lasidiplodia spp. as a causative agent of citrus mortality (El-Ganainy et al, 2022). These studies show that citrus dieback is a multifactorial disease that requires further investigation and management.…”
Section: Introductionmentioning
confidence: 79%
“…For example, eight distinct Lasiodiplodia species were identified on table grape dieback in Brazil [28]. Four species of Lasiodiplodia were associated with M indica, Citrus reticulata, C. sinensis, Ficus carica, Prunus persica, Prunus armeniaca and Pyrus communis trees dieback [29]. Taking adavantge of new sequencing methods could be useful for accurately detecting and analyzing the microbiota associated to diseased orchards.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, studies on Lasiodiplodia have focused on pathogenic species, likely due to the agroeconomic impact of the fungus. Additionally, the high morphological variability among species makes it difficult to reliably distinguish differences between Lasiodiplodia species [ 39 , 46 ]. Macro and micromorphology identification were performed to support the phylogenetic reconstruction.…”
Section: Discussionmentioning
confidence: 99%